Prospects for the New Capital City Policy in Law and Economic Perspectives - Muhammad Kamal (Susbtantive Justice International Journal of Law, 2022)
The relocation of the nation's capital city has been a dream for a long time, but it was only realized after 77 years of Indonesia's independence through Law No. 3 of 2022 concerning the State Capital (IKN Law). Nevertheless, the policy needs to be studied, considering that the current capital relocation will be carried out in the midst of various domestic polemics, as well as global issues such as inflation and the weakening of the global economy after COVID-19, as well as the war between Russia and Ukraine. This study uses a socio-legal research method by combining an interdisciplinary approach between normative studies and economic studies through an analysis of opportunities, threats, strengths, and weaknesses (SWOT). The findings reveal that, from a law perspective, the policy of the new capital city in the IKN Law is an obligation that must be carried out by the government, regardless of who will serve in the future. However, there are several notes to the IKN Law that are not yet in line with the principles of legislation. Meanwhile, from an economic perspective, the IKN policy is indeed based on the ideals of economic equity and sustainability, but financial factors, foreign debt, and global inflation are still a serious threat to the sustainability of the current New capital city policy and for the next few years.